2021
DOI: 10.3390/coatings11050520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rejuvenating Agent on the Pavement Properties of Cold Recycled Mixture with Bitmen Emulsion

Abstract: A traditional cold recycled mixture with bitumen emulsion (CRMB) has a relatively low cracking resistance and moisture susceptibility, which greatly limits its application scope. A rejuvenating agent was employed to improve the pavement properties of CRMB. To avoid the rejuvenating agent having an adverse effect on the new bitumen, reclaimed asphalt pavement (RAP) was firstly treated by the rejuvenating agent, and the effect of rejuvenating time on the pavement properties of CRMB was investigated. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In previous studies [62][63][64], the aged asphalt binder in the RAP was considered to be inactive and a part of the RAP particles. No extra heating was used to melt the aged asphalt in the mixing of CRM, and RAP was employed as "black aggregates" [18]. In the RAP, mineral aggregates were coated with aged asphalt film which does not contribute to the internal cohesion of the mixture.…”
Section: Rap and Rai Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies [62][63][64], the aged asphalt binder in the RAP was considered to be inactive and a part of the RAP particles. No extra heating was used to melt the aged asphalt in the mixing of CRM, and RAP was employed as "black aggregates" [18]. In the RAP, mineral aggregates were coated with aged asphalt film which does not contribute to the internal cohesion of the mixture.…”
Section: Rap and Rai Materialsmentioning
confidence: 99%
“…More recent studies [16,17] also assessed the possibility of incorporating up to 100% of RAP in fully recycled mixtures. As a result of these advantages, CRM is increasingly favored in pavement construction and rehabilitation [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the rejuvenation technology of RAP in foreign countries has been relatively mature, especially in the United States and Japan, where they are improving the utilization rate of old asphalt; asphalt material aging and rejuvenation mechanism research is more mature [24][25][26][27]. However, the research on RAP rejuvenation started late in China, but has developed rapidly in recent years [28][29][30]. Studies on diffusion characteristics are mainly divided into macro experiment and microanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, the recycling of reclaimed asphalt pavement (RAP) in a cold recycled mixture (CRM) with bitumen emulsion (BE) or foamed bitumen is one of the most effective and low-environmental impact technologies [15,16]. The life cycle assessment studies [17] revealed that the CRM technologies reduced the energy consumption by 56-64%, and decreased the greenhouse gas (GHG) emissions by 39-46%.…”
Section: Introductionmentioning
confidence: 99%